Pelatihan Penyusunan Soal HOTS (Higher Order Thinking Skills) Bagi Guru SMK Akuntansi Se-Kabupaten Tulungagung - Umi Nuraini; Dudung Ma’ruf Nuris; Primasa Minerva Nagari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The problem faced by Vocational High Schools Accounting teachers in Tulungagung Regency is that the concept of higher order thinking skills has not been implemented optimally in compiling accounting questions. The purpose of holding this community service is to increase understanding of by Vocational High Schools Accounting teachers in compiling accounting questions based on higher order thinking skills. The method of community service activities is in the form of training for members of the Vocational High Schools Accounting Teachers Organization in Tulungagung Regency. This activity consists of the preparation stage, the implementation stage, and the monitoring and evaluation stage. The results of the evaluation of this activity showed that vocational Accounting teachers in Tulungagung Regency had a better understanding of the concept of higher order thinking skills and their application in compiling accounting questions.